2016
DOI: 10.1186/s12885-016-2908-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal alterations in health-related quality of life and its impact on the clinical course of patients with advanced hepatocellular carcinoma receiving sorafenib treatment

Abstract: BackgroundThis study aimed to identify the health-related quality of life (HRQOL) domains associated with prognosis by assessing longitudinal alterations in HRQOL in patients with advanced hepatocellular carcinoma receiving sorafenib.MethodsWe prospectively assessed HRQOL by administering the SF-36 questionnaire 3-monthly to consecutive patients with advanced hepatocellular carcinoma receiving sorafenib. We evaluated the impact of HRQOL on their overall survival and duration of treatment with sorafenib using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
(39 reference statements)
2
11
0
Order By: Relevance
“…However, time trends for means estimated by GEE in the most dimensions of QoL did not demonstrate significant changes, which were in line with previous studies (Klein et al, ; Shomura et al, ). But we found that the physical and cognitive functioning significantly decreased in 1 month after treatment, which was consistent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, time trends for means estimated by GEE in the most dimensions of QoL did not demonstrate significant changes, which were in line with previous studies (Klein et al, ; Shomura et al, ). But we found that the physical and cognitive functioning significantly decreased in 1 month after treatment, which was consistent.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies mostly examined the effectiveness of different treatments in LC patients (Chie et al, 2015;Kolligs et al, 2015), and few studies explored the factors associated with QoL after treatments (Heits et al, 2015;Lai et al, 2007;Shomura et al, 2016;Shun et al, 2012). However, little is known about the changes in different dimensions of QoL and the specific factors associated with the changes in distinct dimensions of QoL from diagnosis to completed treatments.…”
mentioning
confidence: 99%
“…Therefore, and because wellbeing is an important check for a favorable benefit-harm ratio of the ongoing treatment, general wellbeing and health related quality of life scores are increasingly used as outcome measures for clinical studies in long-term care, oncology, cardiology, and surgery [ 6 9 11 ]. These studies showed that subjective health and wellbeing ratings can also be predictive for the intervention-related burden patients can withstand and still adhere to, for example in chemotherapeutic treatment regimens [ 13 ]. However, apart from research purposes, generic wellbeing assessment before and after treatment is still rarely used as PROM in most highly specialized medical services [ 4 10 ].…”
Section: Predictive Value Of Promsmentioning
confidence: 99%
“…QOL is increasingly being adopted as a measure of the effects of medical interventions, with medical workers no longer relying solely on the length of life as a measure; this can be attributed to the transformation of the modern medical model . QOL evaluations can be used not only to monitor the disease itself but also to evaluate the effects of treatment the physiological, social, environmental, and psychological aspects of patients . Among MSM with HIV/AIDS, the chronic and debilitating nature of HIV/AIDS and the particularity of homosexual transmission cause the infected person to suffer not only physically but also psychologically, leading to an overall decrement in QOL .…”
Section: Introductionmentioning
confidence: 99%
“…15 QOL evaluations can be used not only to monitor the disease itself but also to evaluate the effects of treatment the physiological, social, environmental, and psychological aspects of patients. 16 Among MSM with HIV/AIDS, the chronic and debilitating nature of HIV/AIDS and the particularity of homosexual transmission cause the infected person to suffer not only physically but also psychologically, leading to an overall decrement in QOL. 17 People with HIV/AIDS are socially vulnerable groups-they are often the target of discrimination, and many become marginalized from all aspects of society; as such, their QOL tends to be lower than that of normal people.…”
mentioning
confidence: 99%